Biopsy-proven fungal pyelonephritis complicating delayed graft function in a renal transplant patient. Issue 2 (10th February 2023) - Jesuthasan, Aaron; Roufosse, Candice; Ramaswami, Arun
Abstract : Delayed graft function (DGF) is a common phenomenon following renal transplantation, which can be due to several factors. A rare cause includes invasive fungal infections, which can often be a challenge to diagnose. Nonetheless, prompt identification of such infections particularly within transplant patients is essential as they can lead to severe downstream sequelae, including graft loss and even death. We describe here a challenging case of fungal pyelonephritis complicating and potentially leading to DGF and further dialysis dependence within a renal transplant patient. Notably, we highlight the importance and clinical utility of biopsy to confirm the diagnosis, as investigations may be largely normal otherwise. Furthermore, we emphasise that with early identification of these infections, effective antifungal treatment can be commenced in a timely fashion leading to better patient outcomes and good graft function.